NSeq: a multithreaded Java application for finding positioned nucleosomes from sequencing data - Nellore, Abhinav; Bobkov, Konstantin; Howe, Elizabeth; Pankov, Aleksandr; Diaz, Aaron; Song, Jun S. (Frontiers in Genetics, 2013)
We introduce NSeq, a fast and efficient Java application for finding positioned nucleosomes from the high-throughput sequencing of MNase-digested mononucleosomal DNA. NSeq includes a user-friendly graphical interface, computes false discovery rates for candidate nucleosomes from Monte Carlo simulations, plots nucleosome coverage and centers, and exploits the availability of multiple processor cores by parallelizing its computations. Java binaries and source code are freely available at https://github.com/songlab/NSeq. The software is supported on all major platforms equipped with Java Runtime Environment 6 or later.